The Function of Subordination in Creating Effective Speeches - Tahseen Hameed, may (Journal of College of Education, 2020)
The aim of the study is to investigate subordination as an important tool in effective speeches and to find out the role they play and if it enhances theirmeaning . A sample of two speeches were chosen to show which type of subordination is most prominent ,writers uses subordination as a feature for their language they have a message they want to deliver ,speakers also do . The model of the analysis is guided by functional grammar of Halliday (2004).Subordination is the grammatical arrangement of functionally similar but  unequal constructs in a complex sentence as Fish defines it (2011:51). It creates strong pauses ,writers use subordination when they want to give logical, causal or temporal relationships within clauses so in writing it is used effectively as a device for persuasion and argument ,speakers also needs to be arguers and persuasive .
Keywords: Keywords :.subordinators , logical relation , grammatical complexity ,functional.